Pengaruh Penambahan Puree Labu Kuning (Cucurbita Moschata Ducheness) terhadap Kualitas Fisik dan Mutu Sensori pada Waffle - Siti Rahmadina Izzati; I Gusti Ayu Ngurah; Rina Febriana (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
This research aims to determine the physical and organoleptic quality with the treatment of adding 10%, 20%, and 30% pumpkin puree. The research started from August 2023 to January 2024 in the Food Processing Laboratory of the Culinary Education Program, Faculty of Engineering, Universitas Negeri Jakarta. This study uses an experimental method. The samples in this study are waffles with the addition of 10%, 20%, and 30% pumpkin puree. The data collection in this study uses a hedonic quality test, where 45 somewhat trained panelists evaluate all aspects of the organoleptic quality of the pumpkin puree waffle samples. The data collection techniques used are organoleptic and physical tests. The physical test instrument includes elements measured three (3) times, and the organoleptic evaluation instrument uses measurements with a five (5) point scale range, indicating the highest score down to one (1) for the lowest score. Based on the statistical hypothesis test results, there is a significant effect on the aspects of the inner color, outer color, waffle taste, pumpkin taste, inner texture of the waffle, and pumpkin aroma, followed by a Tukey test. The highest average score in the hedonic quality test for the inner color aspect is 4, and for the waffle taste aspect is 4.6.